2018
DOI: 10.4077/cjp.2018.bag567
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Exercise with Blood Flow Restriction Increases Muscle Strength without Altering hsCRP and Fibrinogen Levels in Healthy Subjects

Abstract: Strengthening exercise combined with blood flow restriction potentially increases muscle strength. This type of exercise does not require heavy weight liftings and is a feasible method to be performed by persons suffering illnesses. However, strengthening exercise may induce inflammatory responses due to muscle and vascular endothelial damage. This study aimed to investigate alterations of high-sensitivity C-reactive protein (hsCRP) and fibrinogen levels in healthy subjects after five weeks of low intensity re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…1,61 The anaerobic conditions of BFR induce an angiogenic stimulus through upregulation of vascular endothelial growth factor. 19,38 In addition, the hypoxic stimuli may stimulate the mobilization and recruitment of endothelial progenitor stem cells, improving the regenerative potential in healthy volunteers. 54 The muscle hypertrophy induced during low-intensity resistance training with BFR is an attractive method of postsurgical rehabilitation in ACLR in that it avoids placing high loads on the graft in the immediate postoperative period and provides rehabilitation options for the elderly and other patients with severe endurance or strength deficiency.…”
mentioning
confidence: 99%
“…1,61 The anaerobic conditions of BFR induce an angiogenic stimulus through upregulation of vascular endothelial growth factor. 19,38 In addition, the hypoxic stimuli may stimulate the mobilization and recruitment of endothelial progenitor stem cells, improving the regenerative potential in healthy volunteers. 54 The muscle hypertrophy induced during low-intensity resistance training with BFR is an attractive method of postsurgical rehabilitation in ACLR in that it avoids placing high loads on the graft in the immediate postoperative period and provides rehabilitation options for the elderly and other patients with severe endurance or strength deficiency.…”
mentioning
confidence: 99%
“…The BF voice therapy is started to be reported in the literature with a good result, that is the improvement of vocal cord deviation. According to the previous study, it was reported that 21 normal persons and 7 patients with vocal nodule who underwent the BF therapy session shows that there are a significant difference in EMG score, and the decrease level of muscle tension 13 . It revealed that there were positive correlation between the EMG result with the voice quality assessment.…”
Section: Introductionmentioning
confidence: 96%
“…This is derived from various blood markers such as D-dimer, fibrin degradation product (FDP), fibrinogen, and prothrombin time, all of which indicate coagulation activity. These factors do not appear to be influenced acutely [100,103,228], or chronically [54,169], following a period of BFR exercise/training.…”
Section: Safety Issuesmentioning
confidence: 86%
“…In human skeletal muscle, it appears that periods of ischemia followed by reperfusion of up to 1.5 hours can be tolerated without any sign of structural, ultrastructural or immunohistochemical damage [271]. Given that the duration of BFR exercise is typically below 30 minutes [292], and doesn't involve complete occlusion of arterial blood flow [189], this may explain why studies investigating the potential for ischemic-reperfusion injury with BFR have failed to note elevations in markers of oxidative stress or inflammation that typically present with this injury [54,169].…”
Section: Safety Issuesmentioning
confidence: 99%
See 1 more Smart Citation